Ruderal: Transformation of terrain vague through framing graffiti and spontaneous vegetation - Dorresteijn, Hugo Lawrence (My University, 2025)
This thesis investigates the unique phenomena of graffiti and ruderal vegetation occurring in the vacant lots of the post-industrial landscape. Defined by architect Ignasi de Solà-Morales Rubió as terrain vague, these spaces foster an emergence of spontaneous phenomena through their abandonment and neglect, turning our city’s wastelands into their wilderness. However, the inevitable redevelopment of these spaces frequently overlooks their role in enabling these phenomena, despite significant social and ecological potential. This research aimed to compile and develop architecturally focused knowledge on graffiti and ruderal vegetation as an alternative approach to transformation of terrain vague. And through this process, generate architectural design strategies capable of amplifying their potential and shifting their perception within architectural discourse. The methodology was guided by the research question; how can architectural design transform terrain vague through amplifying graffiti and ruderal vegetation? Observations and architectural documentation of these phenomena throughout Gothenburg’s industrial harbor, resulted in a series of spatial principles explaining their relationship with architecture. Key findings reveal how the appearance of graffiti is influenced by accessibility, visibility and surface conditions, while ruderal vegetation responds to disturbance patterns, maintenance and substrate availability. A review of theory and case studies underscored the importance of communicating intentionality in gaining public acceptance of these phenomena. With findings suggesting this can be achieved through framing them with a formal language symbolizing care or embracing their wildness. Based on these findings a series of design explorations were generated, culminating in a speculative architectural proposal. The design outcome functions as a framework for user-led adaptation, facilitating and framing spontaneous phenomena in such a way that the proposed space remains functional and attractive. In developing a design vocabulary for graffiti and ruderal vegetation, this research contributes an alternative approach to terrain vague, providing a basis for future projects navigating this context and the interaction between architecture, graffiti and ruderal vegetation.
Keywords: Graffiti, ruderal vegetation, terrain vague, post industrial transformation